1996
DOI: 10.1111/j.1365-2044.1996.tb07694.x
|View full text |Cite
|
Sign up to set email alerts
|

Middle latency auditory evoked potentials during repeated transitions from consciousness to unconsciousness

Abstract: SummaryWe have investigated the relationship between changes in the middle latency auditory evokedpotentials during alternating periods of consciousness and unconsciousness produced by propofol infusion combined with spinal anaesthesia for total knee replacement. Eleven patients completed the study, of whom two had recollection of events after the onset of the anaesthetic. There were no SigniJicant diyerences in heart rate or systolic arterial pressure between any conscious and unconscious period. With the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Similarly, it is known from the midlatency auditory evoked responses that Pa and Nb components, occurring approximately 30 and 40 msec post-stimulus, are promising markers for changes in consciousness during anesthesia. 26 However, the generators of the later MnSSER components are still debated and the nomenclature differs in relation to different recording techniques. 27 However, they have been shown to be early markers for cognitive impairment in patients with hepatic encephalopathy for example.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is known from the midlatency auditory evoked responses that Pa and Nb components, occurring approximately 30 and 40 msec post-stimulus, are promising markers for changes in consciousness during anesthesia. 26 However, the generators of the later MnSSER components are still debated and the nomenclature differs in relation to different recording techniques. 27 However, they have been shown to be early markers for cognitive impairment in patients with hepatic encephalopathy for example.…”
Section: Discussionmentioning
confidence: 99%
“…When propofol infusion produces unconsciousness (as judged by loss of both the eyelash reflex and the response to command), Davies et al [88] observed an increase in the latencies of Na, Pa and Nb, which is reversible and reproducible during alternating periods of consciousness and unconsciousness. Schwender et al [89] also observed that during anaesthesia for Caesarean section, a prominent MLAEP is associated with intra-operative wakefulness, purposeful movements and postoperative recall of surgical manipulation.…”
Section: Influence Of Anaesthetic Drugs On Sepsmentioning
confidence: 99%
“…The AEP were obtained using a similar system to that described in our previous studies [15,20] from three electrodes (Zipprep) placed on the right mastoid (þ), middle forehead (¹) and Fp2 as the reference. The amplifier was custom-built with a 5-kV medical grade isolation.…”
Section: Auditory Evoked Potentials Acquisitionmentioning
confidence: 99%
“…Middle latency auditory evoked potential (MLAEP) has been reported to correlate well with anaesthetic depth [14] and to be able to demonstrate potential awareness [15,16]. However, the MLAEP are usually obtained intermittently and the waveforms are difficult to use in the clinical situation.…”
mentioning
confidence: 99%